2018
DOI: 10.1016/j.nima.2018.02.054
|View full text |Cite
|
Sign up to set email alerts
|

General features of experiments on the dynamics of laser-driven electron–positron beams

Abstract: The experimental study of the dynamics of neutral electron-positron beams is an emerging area of research, enabled by the recent results on the generation of this exotic state of matter in the laboratory. Electron-positron beams and plasmas are believed to play a major role in the dynamics of extreme astrophysical objects such as supermassive black holes and pulsars. For instance, they are believed to be the main constituents of a large number of astrophysical jets, and they have been proposed to significantly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The applicability of LWFA-driven positrons to advanced accelerator concepts is currently subject of investigation, and our recent work [3,4,6], together with that of independent groups [7,8], confirms that there is significant potential in this area. We have also confirmed that such positron beams can be used for some specific studies in laboratory astrophysics, and we have already experimentally measured plasmalike behavior of LWFAdriven electron-positron beams [9][10][11][12]. .…”
supporting
confidence: 66%
“…The applicability of LWFA-driven positrons to advanced accelerator concepts is currently subject of investigation, and our recent work [3,4,6], together with that of independent groups [7,8], confirms that there is significant potential in this area. We have also confirmed that such positron beams can be used for some specific studies in laboratory astrophysics, and we have already experimentally measured plasmalike behavior of LWFAdriven electron-positron beams [9][10][11][12]. .…”
supporting
confidence: 66%
“…The first observation of collective behavior of an electronpositron plasma has been recently reported by Warwick et al [110] and Warwick et al [111]. In this work, a neutral electron-positron beam was propagated through a low-density background plasma, resulting in the growth of a current-driven instability and the generation of strong magnetic fields (≥ 1 T).…”
Section: Prospectsmentioning
confidence: 84%
“…Some progress on overcoming these challenges has recently been achieved [17][18][19][20][21][22][23][24][25][26][27][28] (see also [29] and references cited therein). Experiments [30,31] also demonstrated that the electron beams used for positron production in conventional accelerators can be substituted by electron beams produced in a laser-plasma accelerator (LPA).…”
Section: Introductionmentioning
confidence: 99%